LEARNING MOTIVATION AND PERCEPTION OF THE TEACHERS’ PEDAGOGIC COMPETENCE AND LEARNING ACHIEVEMENT IN SOCIAL SCIENCE OF JUNIOR HIGH SCHOOL STUDENTS - Dhiu, Konstantinus Dua (Universitas Pendidikan Ganesha, 2017)
This present study aims at investigating the relation between learning motivation and junior secondary level students’ learning achievement in social science, figuring out the relation between learning motivation and teachers’ pedagogic competence toward the students learning achievement. A number of 70 students are randomly selected as the sample of this study. The data are collected through questionnaire. This study reveals that; 1) the positive and significant relation between learning motivation altogether with teachers’ pedagogic competence and students learning achievement in social science subject, 2) a positive and significant relation between learning motivation and the perception of teachers’ pedagogic competence toward the students learning achievement in social science subject.